Analysis of the variables that promote professional insertion based on critical thinking - Parra-González, María Elena; Rodríguez-Sabiote, Clemente; Aguaded-Ramírez, Eva María; Cuevas-Rincón, Jesús Manuel (Frontiers in Education, 2023)
Critical thinking is currently one of the most demanded competencies and skills in professionals and, therefore, constitutes one of the fundamental aspects to be developed by educational systems. This is especially important for the development of work tools for future labor insertion. The first objective of the present study was to determine the demographic variables (school type, gender, level education, work experience and volunteering) that can be used to predict the development of critical thinking in students undertaking vocational training or secondary education. The second objective was to determine whether the variables considered to be the most effective predictors are able to distinguish between higher and lower levels of critical thinking. For this purpose, a sample of students undertaking vocational training or secondary education in southern Spain (n=3.132) was recruited. A quantitative study was then conducted, performing regression and decision tree analysis to identify predictors. Based on study outcomes, it can be concluded that a need exists to work on critical thinking at these educational stages and throughout life whilst considering the variables that influence critical thinking such as educational level, work experience and volunteering.